Types of tourists and tourism practices during the Olympic Games. - Marie Delaplace; Alexandra Schaffar (Via@)
The Olympic and Paralympic Games raise many expectations for tourism dynamism in host cities. However, the scientific literature shows that there is not always an expansion of tourism due to a possible crowding out effect of tourists: the anticipated congestion and the increase in accommodation rates discourage tourists from coming to the host city during this period. Moreover, tourists interested in the Olympic Games are likely to have specific characteristics and practices. Paris, one of the world’s leading tourist cities, will host the Games in 2024. In order to identify the characteristics and practices of tourists likely to be present at that time, a survey was carried out in 2019 with 1,265 international and French tourists. The statistical analyses conducted on the data obtained (multiple component analysis, dendrogram and linear regression model) allow us to characterize both the tourists who will come and those who will not as well as their respective practices, in particular concerning the visited sites.